ChemInform Abstract: Catalytic Enantioselective 1, 3‐Dipolar Cycloadditions of Azomethine Ylides for Biology‐Oriented Synthesis. Issue 25 (24th June 2014) - Narayan, Rishikesh; Potowski, Marco; Jia, Zhi‐Jun; Antonchick, Andrey P.; Waldmann, Herbert
Abstract Review: 37 refs.